Age-related patterns of anthropometric characteristics in young wrestlers - Camic, C. L.; Housh, T. J.; Mielke, M.; Hendrix, C. R.; Zuniga, J. M.; Johnson, G. O.; Housh, D. J.; Schmidt, R. J. (Medicine & Science in Sports & Exercise, 2009)
Purpose: The purpose of the present study was to compare the age-related patterns of anthropometric characteristics in young wrestlers (8-13 yr) to those of a national representative sample of boys the same age.